2022
DOI: 10.21511/pmf.11(1).2022.03
|View full text |Cite
|
Sign up to set email alerts
|

Development of financial inclusion from the standpoint of ensuring financial stability

Abstract: Since 2013–2015, financial inclusion has been considered a determinant of economic and social inclusion. Meanwhile, the impact of financial inclusion on economic development directly depends on financial stability. This paper focuses on the development peculiarities of financial inclusion in relation to ensuring financial stability and provides recommendations to Ukraine. The inclusive development theory and gap theory form the theoretical research base, while generalization, statistical methods, coefficient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
1
18
0
2
Order By: Relevance
“…The indicators of external debt security were assessed, and the predicted values of individual indices were calculated, taking into account the current state of the economy of Ukraine. Kuznyetsova et al (2022), considering the "Stockholm Principles," indicated the importance of researching the impact of individual macroeconomic and financial risks in the economy of Ukraine on the level of debt security. In addition, the procedure for forecasting the public debt of Ukraine using the ARIMA model was illustrated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The indicators of external debt security were assessed, and the predicted values of individual indices were calculated, taking into account the current state of the economy of Ukraine. Kuznyetsova et al (2022), considering the "Stockholm Principles," indicated the importance of researching the impact of individual macroeconomic and financial risks in the economy of Ukraine on the level of debt security. In addition, the procedure for forecasting the public debt of Ukraine using the ARIMA model was illustrated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors Аngela Kuznyetsova, Іryna Boiarko, Мyroslava Khutorna and Yuliia Zhezherun (2022) [18] investigated the peculiarities of the development of financial inclusion cross-country analysis taking into account different models of the financial system and economy levels of development. It was established that the weaknesses of financial inclusion in Ukraine are a seven-fold gap between the assets of banks and non-bank financial institutions and 37% adult population without banking services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digitalization not only helps to overcome the information asymmetry between businesses and investors (Pedchenko et al, 2018) but also stimulates the development of SMEs in other business aspects. For example, the digitalization of banking services (Pham et al, 2022;Kuznyetsova et al, 2022), the insurance market (Polinkevych et al, 2021), and the chatbots (Jansom et al, 2022) became significantly more developed during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%